COFFEE PRODUCT MARKETING ASSISTANCE TO BABADAN MERAPI COFFEE SMEs - Damar Irsyad Ustadz; Achmad Nur Alfianto; Achmad Labib (khidmatan, 2022)
Most MSMEs in rural areas utilize and increase the value of local raw materials to produce a product. Utilization of local raw materials as superior products for SMEs in Magelang Regency, such as in the Dukun District, more precisely in Paten Dusun Babadan 2. One of the SMEs that utilizes local raw materials is Arabica coffee bean processing. Products produced from these raw materials can also be quite a lot. However, good marketing has yet to support the amount of product produced. This is due to the need for more marketing personnel and the absence of a food product brand. Based on this, the servant assists the MSMEs in marketing strategies. The method used is ABCD Asset-based research. In assisting marketing activities, servants provide training on using social media as a marketing tool and making product labels or brands that become the identity of Arabica coffee bean processing products in Babadan village.